Keterampilan Pemimpin dalam Komunikasi dan Pengambilan Keputusan Berdasarkan Nilai-Nilai Islam dalam Konteks Pendidikan - Mahdalena Juniarsih; Ahmad Hendrawan; Aa Nugraha; Raihan Nuryasa Fartusi; Ika Kartika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is to determine leaders' skills in communication and decision making based on Islamic values ​​in an educational context. The method used is a qualitative methodology with data collected through the library research method. The data obtained in this method is based on facts, reality in the field and not designed by researchers through research research. The results of this research are that the success of a leader in influencing by using influencing tactics is largely determined by the leader's skills and experience. Leaders who have high skills and experience are easier to influence than those with low skills and experience. Leaders must understand various influencing tactics or strategies and how to use each influencing tactic. If with these influencing tactics or strategies the target/people influenced are influenced and change their attitudes, behavior and thought patterns, then the leader has succeeded in influencing the target and the influencing process is complete.